The care provided by the family to the premature newborn: analysis under Leininger's Transcultural Theory - Ana Celi Silva Torres Nascimento; Aisiane Cedraz Morais; Rita da Cruz Amorim; Deisy Vital dos Santos (Associação Brasileira de Enfermagem, 2020)
ABSTRACT Objective: To analyze the care practices of family members of premature infants admitted to a Neonatal Intensive Care Unit in the light of Leininger's transcultural theory. Methods: Qualitative, descriptive and exploratory study. Participant observation and semi-structured interviews were conducted with 16 family members of newborns, admitted to the neonatal unit of a public maternity hospital, during the months of May and June 2019. The software called Interface de R pour analyses Multidimensionnelles de Textes et de Questionnaire ® and the Bardin Content Analysis technique. Results: Two thematic categories emerged: Family care in the neonatal unit; (in)effective support for shared care. Conclusion: The participation of families in the care of babies is still unstable, but it must be an inseparable element of culturally congruent care, thus collaborating with the full recovery of the premature.